2022
DOI: 10.3389/fonc.2022.925582
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of VHL and SDHA Pathogenic Variants: A Case Report

Abstract: Von Hippel Lindau(VHL)syndrome presents with cerebellar and spinal hemangioblastomas, renal cell cancer, neuroendocrine pancreatic tumor, and pheochromocytoma and it is caused by germline mutations in the VHL gene. Pathogenic germline variants in the succinate dehydrogenase A (SDHA) gene are associated with paraganglioma and pheochromocytoma. Here we report co-occurrence of germline pathogenic variants in both VHL and SDHA genes in a patient who presented with pancreatic neuroendocrine tumor. As these genes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some studies have also demonstrated that CHEK2 germline mutations could be detected in early-onset RCC or associated with renal cancer 30 36. Coincidentally, a recent case report showed that an earlier age of onset of pancreatic neuroendocrine tumour was observed in a patient with both VHL and SDHA germline mutations 37. These alterations could be genetic modifier factors that protect or aggravate the phenotype in patients with VHL disease, which needed further basic research to identify.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also demonstrated that CHEK2 germline mutations could be detected in early-onset RCC or associated with renal cancer 30 36. Coincidentally, a recent case report showed that an earlier age of onset of pancreatic neuroendocrine tumour was observed in a patient with both VHL and SDHA germline mutations 37. These alterations could be genetic modifier factors that protect or aggravate the phenotype in patients with VHL disease, which needed further basic research to identify.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations to each subunit or SDHAF2 have been linked to developing SHD-RCC, with SDHB being the most common [ 101 , 102 , 103 ]. Recently, a patient presenting with pancreatic neuroendocrine tumors was noted to have mutations to both SDHA and VHL , but it is unknown how potential RCC tumors would behave with this dual mutation burden [ 104 ]. Succinate dehydrogenase is unique in that it functions as both a key component of the Kreb’s/Tricarboxylic acid (TCA) cycle and the electron transport chain as Complex II, thus placing the tetramer at the center of cell metabolism [ 105 ].…”
Section: Succinate Dehydrogenase-deficient Renal Cell Carcinoma (Sdh-...mentioning
confidence: 99%